Peran Website UINSU Library Dalam Mewujudkan Perpustakaan Digital Di Era Global - Najwa Alifah Zulfikar Damanik; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
Digital libraries are emerging as a significant way to solve the problem of information accessibility and the demand for current and relevant knowledge in a rapidly changing information age. The website of the State Islamic University of North Sumatra was chosen as a research topic because of its strategic significance in providing students, instructors, and university personnel with broad access to digital collections, library services, and academic materials. Researchers can collect and examine data from various sources related to research problems by using systematic literature reviews as their research approach. The website of the State Islamic University of North Sumatra has contributed significantly to improving information accessibility, making digital collections more widely available, and improving overall library services, according to the findings of a literature review analysis.